Production of tetraploid plants of non apomictic citrus genotypes - Aleza, Pablo; Juárez, José; Ollitrault, Patrick; Navarro, Luis (2017)
Ploidy manipulation in Citrus is a major issue of current breeding programs aiming to develop triploid seedless mandarins to address consumer demands for seedless fruits. The most effective method to obtain triploid hybrids is to pollinate tetraploid non apomictic cultivars with pollen of diploid varieties. Such non apomictic tetraploid lines are not found in the citrus germplasm and need to be created. In this work we describe a new methodology based on in vitro shoot-tip grafting combined with treatment of the micro-grafted shoot-tip with colchicine and oryzalin to achieve chromosome doubling and a dechimerization procedure assisted by flow cytometry. Stable tetraploid plants of Clemenules, Fina and Marisol clementines and Moncada mandarin have been obtained directly from shoot tip grafting combined with colchicine and oryzalin treatments or after dechimerization of mixoploids plants (2x-4x). These stable tetraploid plants have been used in 4x x 2x hybridizations, to recover over 3,250 triploid hybrids in 3 years.